Risk and Protective Factors of Self-Harm and Suicide in Adolescents in The Era of Society 5.0: A Systematic Review - Trihaningsih Puji Astuti; Nurul Hidayati; Fauzi Tsanifiandi; Rr Dian Tristiana (Universitas Airlangga, 2024)
Introduction: Suicide and self-harm have been ranked as the fourth leading causes of mortality among adolescent population. Preventive interventions are necessary due to the rising prevalence. The aimed of this study was to identify the risk and protective factors of self-harm and suicidal behavior among adolescents in the era of society 5.0. Methods: This study was a literature review. Published, English articled were retrieved from Scopus, Web of Science, PubMed, and CINAHL databases, limited to the last five years from 2018 to 2023. The specific keywords used to search for articles were (